2020
DOI: 10.1371/journal.pone.0244175
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of fast innovation under the pressure of COVID-19

Abstract: Covid-19 has rapidly redefined the agenda of technological research and development both for academics and practitioners. If the medical scientific publication system has promptly reacted to this new situation, other domains, particularly in new technologies, struggle to map what is happening in their contexts. The pandemic has created the need for a rapid detection of technological convergence phenomena, but at the same time it has made clear that this task is impossible on the basis of traditional patent and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The obtained results also confirmed conclusions concerning rapid technological innovations occurring under the pressure of the COVID-19 pandemic, which applied mainly to remote control, remote working, telemedicine and remote learning [121]. It was found that, in the studied organizations, the jump was sudden and produced many important effects for project management.…”
Section: Discussionsupporting
confidence: 80%
“…The obtained results also confirmed conclusions concerning rapid technological innovations occurring under the pressure of the COVID-19 pandemic, which applied mainly to remote control, remote working, telemedicine and remote learning [121]. It was found that, in the studied organizations, the jump was sudden and produced many important effects for project management.…”
Section: Discussionsupporting
confidence: 80%
“…They can be used for a number of reasons, which include sharing information about products, decisions, strategies [85], and for accountability on the firms' economic, environmental, and social activities. During the pandemic, the quantity of data being shared online increased, with online social networks strengthening their role as a mean of communication [86]. First, we show that online social media are a tool to capture firms' issues, challenges and concerns, highlighting groups of firms that are facing similar challenges in a timely manner.…”
Section: Discussionmentioning
confidence: 84%
“…However, the use of digital technology can also have some negative effects due to the social distancing requirements imposed during the COVID-19 crisis. For example, human labor has been reduced by partially replacing human labor with machines [35], and cybersecurity issues have increased through remote work and the use of online platforms [36]. The coronavirus pandemic has transposed many businesses online, so the companies located in areas with poor access to digital connectivity have limited capacity to develop resilience in difficult economic times [37].…”
Section: Industry 40 Technologies Covid-19 and Digital Resiliencementioning
confidence: 99%